PENINGKATAN KUALITAS PRODUKSI BERBASIS INFORMATION TECHNOLOGY PADA KELOMPOK USAHA CEMILAN MAKANAN RINGAN DI MLATI LOR KUDUS - Puspitasari, Ratih Hesty Utami; Wijayanti, Ratna Yulia; Winarso, Rochmad (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
The business group of cemilan makanan ringan Mlati Lor Kudus is a small industry category or home industry. In the past, the number of entrepreneurs cemilan makanan ringan is quite a lot, but recently they moving in another business, because the manufacturing process is still using human labor in the processing and packaging of products, thus making the saturation of the workers. This would result in a fairly risky to the domestic industry that still uses the traditional system both economically, socially and most importantly the impact on the product. In general, the industry of cemilan makanan ringan is still using muscle power, does not have the records or the calculation of how the number of inputs (raw materials, manufacturing process, labor costs, and overhead costs of production) the truth true for every stage of the process manually. So severalÂ  household industry most of the lack of attention to the cause of the decline in the quality, how alternative steps and actions to be undertaken and effective how the process production, packaging and marketing of products. On the other hand they are also less concerned about the problem of space layout work and the production of space layout is seen quite chaotic and dirty so sometimes causing environmental impacts of production resulting in lower production quality. The application of science and technology activities conducted through in Four Phase which is the unity of a series of activities, namely: Phase 1: the manufacture of tools, PHASE 2: Activity Frying, during the second phase of activitiesundertaken is revamping the layout understanding of the frying pan and safer. Training is done by housekeeping layout training. PHASE 3: Activities Packaging and Labeling Products. Phase 4: Web-based training on marketing products online, Keywords: Industry of Cemilan Makanan Ringan, Application of science and technology, Layout